ASSISTANCE FOR THE IMPROVEMENT OF THE BELOVED PET COMMUNITY WITH GROOMING SKILLS IN AN ARTISTIC MANNER IN PANGKAJENE DISTRICT, PANGKEP REGENCY - DWI KESUMA SARI; AMRIANI, RINI; Dian Fatmawati; Muh. Zulfadillah Sinusi; Arif, Makruf (Jurnal Layanan Masyarakat (Journal of Public Services), 2024)
In the world of veterinary medicine, maintaining the cleanliness of pets is one of the efforts to suppress the occurrence of zoonosis. One effort that can be done is by routinely grooming. Grooming is a hygiene treatment that includes bathing, cleaning ears, cutting nails, and combing hair. However, currently in Pangkep Regency, several problems have been found along with the increase in the number of pet lovers, one of which is the lack of knowledge of owners about the procedures for legitimate grooming. This factor then became the background for the creation of a workshop to empower pet lovers with grooming skills in Pangkep Regency. The purpose of this activity is to transfer knowledge by providing socialization and direct demonstrations regarding the procedures for legitimate grooming of pets to avoid integument diseases and conditions that can trigger the emergence of new diseases after improper grooming in Pangkep Regency. These legitimate grooming procedures can be adopted and utilized by the community, namely basic knowledge of grooming techniques that can be applied directly to pets at home. This will help owners to save on grooming costs for their pets. During the implementation of the activity, a demonstration of legal grooming was carried out on two cats, pocket books were distributed, and educational videos were shown on legal grooming technique guides. Participants who attended were 42 pet owners who were members of the Pangkep pet lovers group, where at the end of the activity session a questionnaire was filled out by the owners. Based on the results of the survey conducted, 39 were able to answer the questions from the questionnaire correctly, the rest were owners who did not follow the activity until the end due to other activities outside the location of this service. This is a reflection of the improvement in legal grooming skills in owners who previously only 8 out of 37 respondents understood the legal grooming aspect.